Manajemen Program Peminatan Peserta Didik Di SMA - Ceri Setiyati; Siti Mariah (Kelola: Jurnal Manajemen Pendidikan, 2019)
The purpose of the study to describe the management of interest programs of learners in the Curriculum 2013 in SMA Negeri 2 Bantul Yogyakarta, including planning, organizing, implementation, and supervision. This type of research is qualitative with data collection techniques: observation, interview, and documentation. Informants are principals, vice principals, teachers, and students. Techniques to check the validity of the data used are observations and triangulation. Data analysis techniques for data reduction, data presentation, and conclusion. The result of the research indicates that the management of the program of the student's interest is well implemented, covering: planning of the program of interest of the learners is done through the formation of the committee, determining the kinds and quota, instrument and budget; organizing determines working mechanisms, division of tasks and creating a conducive environment; implementation is done through the determination of specialization program, learning process and self-development implementation; and supervision through the compilation of curriculum documents, PPDB reports and supervision of learning.